The making of law : the Supreme Court and labor legislation in Mexico, 1875-1931 - Suarez-Potts, William J. (Stanford University Press, 2012)
This study argues that the federal judiciary's adjudication of labour disputes and its elaboration of new legal principles played a significant part in the evolution of Mexico's labour law and the nation's political and social compact. This conclusion might seem paradoxical in a country with a civil law tradition, weak judiciary, authoritarian government, and endemic corruption. The book shows how and why judge-made law mattered, and why contemporaries paid close attention to the rulings of Supreme Court justices in labour cases as the nation's system of industrial relations was established.